Effectiveness of home nursing care in the follow-up of preterm infants after hospital discharge - Rodríguez Molina, Ana María (2018)
Preterm infants admitted to the Neonatal Intensive Care Unit (NICU) must be admitted to a follow-up program to prevent complications during the transition to the home and hospital readmissions. In addition, parents of premature children experience various feelings and challenges when their child arrives home. The objective of this protocol of clinical practice based on evidence is to analyze the best available scientific evidence regarding the effectiveness of nursing home care programs (ADE) for the follow-up of premature NICU graduates. The clinical practice based on evidence was used as a methodology, initially a clinical question of prognostic type was raised and the objectives according to this were raised, based on which a set of descriptors was identified from which it was made the search for scientific evidence in different scientific databases.